2006
DOI: 10.1101/gr.4565806
|View full text |Cite
|
Sign up to set email alerts
|

An initial map of insertion and deletion (INDEL) variation in the human genome

Abstract: Although many studies have been conducted to identify single nucleotide polymorphisms (SNPs) in humans, few studies have been conducted to identify alternative forms of natural genetic variation, such as insertion and deletion (INDEL) polymorphisms. In this report, we describe an initial map of human INDEL variation that contains 415,436 unique INDEL polymorphisms. These INDELs were identified with a computational approach using DNA re-sequencing traces that originally were generated for SNP discovery projects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
458
1
8

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 579 publications
(481 citation statements)
references
References 37 publications
(39 reference statements)
14
458
1
8
Order By: Relevance
“…51,52 Similarly, no large-scale attempt was made to identify indels until 2006, in which a study found several hundreds of thousands of indels in the human genome. 7 The commonness of LOHs or homozygosity regions in the genomes of outbred populations was also under appreciated until the first report appeared in 2006. 2 However, the richness of genetic variations in the human genome has recently been further corroborated by the several whole genome resequencing studies, revealing plenty of new SNPs, indels, CNVs and other structural variations.…”
Section: The Evolution Of Genetic Markers In Disease Gene Mappingmentioning
confidence: 99%
See 2 more Smart Citations
“…51,52 Similarly, no large-scale attempt was made to identify indels until 2006, in which a study found several hundreds of thousands of indels in the human genome. 7 The commonness of LOHs or homozygosity regions in the genomes of outbred populations was also under appreciated until the first report appeared in 2006. 2 However, the richness of genetic variations in the human genome has recently been further corroborated by the several whole genome resequencing studies, revealing plenty of new SNPs, indels, CNVs and other structural variations.…”
Section: The Evolution Of Genetic Markers In Disease Gene Mappingmentioning
confidence: 99%
“…However, no large-scale attempt was made to identify indels until 2006, in which a study identified 415 436 indels with about equal numbers of insertions and deletions. 7 The sizes of these indels ranged from 1 bp to B10 kb (which span the '1 kb boundary'), thus suggesting that the dataset is actually a mixture of indels and CNVs. In addition, the study also found over 148 000 indels located within known genes and several thousands of them are found in the promoter regions and exons of genes.…”
Section: Indelsmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, the only previous study that has characterize small to medium size indels in the human populations is by Mills et al [13]. They used low coverage Sanger-style reads from 36 individuals to identify indels via the split-read mapping approach.…”
Section: Genome Project Pilot Datasetmentioning
confidence: 99%
“…Remarkably, MoGUL was able to identify 83% of the indels > 50bp (20/24) that were previously detected by MoDIL, while identifying several additional variants that were missed by MoDIL, Table 1. Comparison between indel calls in chromosome 20 located by our approach with the datasets generated by Mills et al [13] (all MoGUL indels), and MoDIL [10] (only indels in NA18507, the same individual as was studied by Lee et al, was considered). For the simulation experiments we consider the indel call is correct if the difference between the true indel size and the predicted one is less than 10bp and the log likelihood ratio is greater than 10. possibly due to low coverage in the NA18507 individual specifically.…”
Section: Genome Project Pilot Datasetmentioning
confidence: 99%